Design and Build Vespa Motorcycle Queue Service System with Android-Based Multi-Channel Single Phase Method: Design and Build Vespa Motorcycle Queue Service System with Android-Based Multi-Channel Single Phase Method - Muhammad Rafli; Fauziah Fauziah; Ratih Titi Komala Sari (Institute of Computer Science (IOCS), 2020)
The queue of the most unpleasant activities for almost everyone in the world, a queue which means waiting for their turn to get service from a facility, such as Vespa motorcycle users who want to get service to repair their vehicles in the garage easily and quickly. Repairs are carried out ranging from minor maintenance to heavy maintenance such as dismounting the engine. The irregularity of existing service queues at Vespa motorcycle workshops makes consumers feel uncomfortable and disadvantaged. Therefore it requires an easy and regular Vespa motorcycle queue service. For this we need a system that can manage the queue service process for users. The method used to regulate services is Multi Channel Single Phase, namely there are two or more service system entry lanes and there is only one service facility in each lane. This method was chosen because it is able to set the queue, speed up the work process and shorten the waiting time for customer service.